How the Electric Toothbrush, Search Engine, Smartphone, Social Media and Artificial Intelligence Decision-Making Processes Amplify the Exercise of Power at State and Global Levels: A Media Ecology Analysis - Krupiy, Tetyana (Tanya) (New Explorations, 2024)
Scholars disagree over whether the employment of artificial intelligence technologies entails an inevitable exercise of power over people or whether such technologies can be configured in such a way as to allow a plurality of possible ways to engage in governance. This article uses the media ecology approach to analysis to demonstrate that the concern that artificial intelligence technologies that appear to be mundane are in fact involved in the exercise of power over people is valid. It contributes to the existing literature by showing that numerous applications of artificial intelligence that people use on an everyday basis interact to amplify one another’s effects. These technologies are the electric toothbrush, internet search engine, smartphone, social media and the use of artificial intelligence as part of the decision-making process. These effects occur at the levels of the individual, city, state and inter-state. These effects are cascading and interconnected rather than occurring on distinct planes. The exercise of power over the individual by the state and the corporations becomes difficult to disentangle. Therefore, states need to cooperate regarding governing artificial intelligence and technology companies if they are to meaningfully protect people from harmful effects.